Stable dicentric autosome, tdic (8:22)(p23:p13), in a mentally retarded girl. - Roberts, S H (1977)
A dicentric autosome, tdic(8:22)(p23:p13), was found in all metaphase cells examined from the peripheral blood of a mentally retarded girl. It is suggested that the centromere of chromosome 22 was inactive, allowing the dicentric to behave as a monocentric element. The involvement of acrocentric chromosomes in the stable dicentric autosomes of man is discussed.